PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. X - Raharja, Kho Susan; Wijono, Sutarto (Universitas Ciputra Surabaya, 2021)
This research aims to find out organizational culture affects employee performance in the company. This research uses quantitative research conducted by jumping directly into the field. The sample used amounted to 37 people taken with non-probability sampling techniques. The study used scale in data collection. The variable scale of employee performance is taken from the scale of Robert, et al (2006) with statement items totaling 24. Organizational culture scale is taken from scale of Robbins (2002) with statement items totaling 23 items. Data analysis is done with the help of SPSS software. The results showed that the value of R = 0.391; p <0.05 which means the influence given by Organizational culture as much as 39.1% on Employee performance and the remaining 60.9% is influenced by other variables that are not in this study. That way, it can be known that organizational culture has a significant role in determining employee performance in PT. X .